Evaluation of the anticoagulant effect of vitamin K antagonists in patients with non-valvular atrial fibrilation - Stanojković, Zoran; Antić, Ana; Balint, Bela; Todorović, Milena; Vučić, Miodrag; Vacić, Nebojša; Lazarević, Milan (Vojnosanitetski pregled, 2021)
Background/Aim. Despite the introduction of new oral anticoagulants (dabigatran, rivoroxaban, apixaban), vitamin K antagonists (VKA), such as warfarin and acenocoumarol are still the most widely used oral anticoagulants for the treatment of nonvalvular atrial fibrillation (NVAF). The time in therapeutic range (TTR) represents a measure of the quality of the anticoagulant effect of these drugs, and it is considered that the lower value of TTR is associated with the adverse effects of therapy. The aim of this study was to evaluate of the effectiveness of VKA therapy in patients with NVAF and to identify factors affecting the anticoagulation efficacy. Methods. A retrospective study was conducted on a population of 725 outpatients with NVAF, treated with VKA and followed in the Blood Transfusion Institute of Niš, Serbia, from January to December 2017. Laboratory control of the INR was done from capillary blood of patients on Thrombotrack Solo (Axis Shield, Norway) and Thrombostat (Behnk Elektronik, Germany). Targeted therapeutic INR was between 2.0 and 3.0. For each patient all available INR values were evaluated to calculate the individual TTR according to the Rosendaal method. Results. The study included a total of 725 patients with NVAF which had 6,105 INR measurements, what was 8.13 ± 2.47 INR measurements per patient. The mean value of TTR and was 60.15 ± 17.52%, but 49.72% of patients had TTR less than 60%. Patients were at high risk of thrombosis in 6.15% of time (INR < 1.5) and high risk of bleeding in 2.2% of time (INR > 4.5). The most significant independent factors affecting the quality of VKA therapy were gender, arterial hypertension, diabetes mellitus and the use of amiodarone and antiplatelet drugs (aspirin, clopidogrel). Conclusion. The TTR is undoubtedly useful indicator of the VKA treatment effectiveness. The most important predictors of poorer efficacy of VKA therapy are: arterial hypertension, diabetes mellitus, patients' gender and the use of amiodarone and antiplatelet drugs (aspirin, clopidogrel). To improve the quality of VKA therapy, education of patients and better collaboration with them, as well as a successful teamwork of clinicians are also imperative.
Keywords: anticoagulants; atrial fibrillation; blood coagulation tests; dose-response relationship, drug; vitamin k